2012
DOI: 10.1371/journal.pone.0031760
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Two-Component System Involved in the Transition to Secondary Metabolism in Streptomyces coelicolor

Abstract: BackgroundBacterial two-component signal transduction regulatory systems are the major set of signalling proteins frequently mediating responses to changes in the environment. They typically consist of a sensor, a membrane-associated histidine kinase and a cytoplasmic response regulator. The membrane-associated sensor detects the environmental signal or stress, whereas the cytoplasmic regulatory protein controls the cellular response usually by gene transcription modulation.Methodology/PrincipalFindingsThe Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 34 publications
1
28
0
2
Order By: Relevance
“…Hybridisation data from RNA extracted at the early stationary phase of growth were very dispersed (not shown), probably due to the bacterial heterogeneity, as observed previously [ 12 , 13 ].…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Hybridisation data from RNA extracted at the early stationary phase of growth were very dispersed (not shown), probably due to the bacterial heterogeneity, as observed previously [ 12 , 13 ].…”
Section: Resultssupporting
confidence: 65%
“…It has been observed that major secretory protein overproduction, constituted mainly of Sec proteins, was triggered by the presence in high copy number of a two-component system regulator in S . coelicolor [ 13 ], as well as the induction of the stringent response, strongly suggesting that when the cell detects nutrient depletion (amino acids by protein overproduction), the stringent response is triggered.…”
Section: Discussionmentioning
confidence: 99%
“…These are among 67 two-component systems encoded in the S. coelicolor chromosome (137). Other two-component systems influencing antibiotic production, but not closely linked to antibiotic biosynthetic genes, include the following: CutRS, affecting ACT production (138); EcrA1A2 (SCO2517 and -8), affecting only RED production (139); SCO0203/0204, which interplay with the orphan RR SCO3818 in exerting medium-dependent effects on ACT production (140,141); and SCO5784 and -5, affecting the timing of ACT and RED production and sporulation, possibly through effects on ppGpp synthesis (142). In two surveys of several two-component systems, the AbrA1A2 system acted negatively on production of ACT, RED, and CDA and the formation of aerial mycelium, while the AbrC1C2C3 system, involving two histidine protein kinases, acted positively on all four aspects (143), and RapA1A2 was shown to stimulate ACT and CPK production (140).…”
Section: Other Two-component Systems Influencing Antibiotic Productionmentioning
confidence: 99%
“…The 16srRNA gene in S. erythraea was used as the positive internal control. RT-qPCR was performed in 25 μL mixtures using a CFX96 ™ real-time PCR detection system (Bio-Rad, Hercules, CA, USA) (Lu et al 2007;Rozas et al 2012;Yu et al 2012). After optimizing the Tm value and Ct value, each sample was analyzed in three replicates.…”
Section: Real-time Quantitative Polymerase Chain Reaction (Rt-qpcr)mentioning
confidence: 99%